Chemical Composition of Natural Fibers Using the Measured True Density. Case Study: Ichu Fibers - Charca S. (2021)
This paper was written in the context of the Project funded by CONCYTEC, under the contract number N° 103-2018 - FONDECYT-BM. The authors of this paper appreciate the financial support from the Peruvian Government.